Wave-assisted propulsion: an experimental study on traveling ships - Chan, ChunYin; Wang, Junxian; Yang, Liang; Zang, Jun (American Institute of Physics (AIP), 2024)
A submerged hydrofoil interacting with incoming waves produces combined heaving and pitching motion, facilitating the conversion of wave energy into thrust. When the foil is attached to the ship hull, the generated “green” power from wave energy could assist the ship's propulsion system and significantly reduce fuel costs. This study experimentally assesses thrust generation from a fixed mid-hull foil by comparing towing force at different wave and traveling speeds. The optimal mid-hull foil demonstrates a fuel cost reduction ranging from 10.3% to 20.4% at diverse traveling speeds and wave parameters. Thrust generation increases at higher traveling speeds. Additionally, this study mathematically describes the hydrofoil motion with an outer pivot, which better suits the ship–foil model. This study then introduces a Strouhal number (⁠StA,S) specifically for the ship–foil model, considering ship travel, ship response, and the hydrofoil's rotation around its outer pivot.
Keywords: Energy consumption; Renewable energy; Wave power; Wave mechanics